The effect of Cymbopogon nardus leaf ash on the setting time of cement paste - Bunyamin, Bunyamin; Mahasin, Abel; Djafar, Tasliati; Sulaiman, Sulaiman; Putra Jaya, Ramadhansyah (Elsevier Ltd, 2026)
The cement industry is a significant global source of CO₂ emissions, driving the need for sustainable supplementary materials. This study investigates the potential of Cymbopogon nardus Leaf Ash (CNLA), an agricultural waste product, as a partial cement replacement to reduce the carbon footprint of construction materials. The effect of CNLA on the bulk density and setting time of cement paste was evaluated at substitution levels of 0 %, 5 %, 10 %, and 15 %. A total of 24 specimens were prepared; bulk density was measured on 5 cm cubes, and setting time was determined using a Vicat apparatus per ASTM standards. Results indicated that substitutions of up to 10 % CNLA had an insignificant effect on the hydration kinetics, with initial and final setting times remaining comparable to the control at 60 and 105 min, respectively. However, a 15 % substitution significantly delayed the setting, increasing the initial and final times to 105 and 135 min. This retardation is attributed to the low calcium oxide (CaO) content and porous microstructure of CNLA, which impedes the hydration process. The findings demonstrate that CNLA can effectively replace up to 10 % of cement without adversely altering the setting characteristics, offering a viable pathway for developing greener construction materials by valorizing local agricultural waste.